Directive skills and school management in regular basic - Baldeón Baldeón, Yrma Yrene (2023)
Management skills focused on leading, directing, and managing the pedagogical and institutional actions of schools have gained relevance in recent years. The objective of the research was to determine the relationship between managerial competencies and school management in regular basic education. The methodology used was quantitative, basic non-experimental correlational, and we could count on the participation of 80 teachers to whom questionnaires validated by expertise were applied. The findings showed moderate significance between the aforementioned variables and in the case of the community dimension a low correlation was determined, and based on this situation it is predisposed as a purpose for organizational improvement in the medium and long term. It was concluded on the importance of consolidating strategic alliances with various institutions in the community for training purposes and pedagogical intentionality.